Bees improve oil quality of oilseed rape - Perrot, Thomas; Bretagnolle, Vincent; Acar, Niyazi; Febvret, Valérie; Matejicek, Annick; Grégoire, Stéphane; Gaba, Sabrina (Basic and applied ecology, 2024)
Global demand for vegetable oil is projected to expand to 28 Mt by 2028. Oilseed rape (OSR) is the predominant oilseed crop in Europe. Its nutritional value is determined by seed oil content and fatty acids (FAs) composition. Insect pollination increases seed oil content, however, its benefit on FAs composition remains unknown. In this study, we address this gap by investigating the variation of OSR seed oil content and FAs composition along a gradient of bee abundance in farmed OSR fields. We used a pollinator exclusion experiment to disentangle the contribution of pollination processes, i.e. wind, self and insect pollination. We show that bees improved OSR nutritional value by increasing amount of poly-unsaturated FAs and decreasing the amount saturated and trans-saturated FAs. In addition, oil content was higher in seeds with than without access to pollinators. Our study provides for the first time, to the best of our knowledge, evidence that insect pollination enhances the quality value of OSR oil by affecting FAs composition. Such effect implies potential negative consequences with any further decline of pollinator abundance. More investigations are also needed to better understand the mechanisms by which insect pollination affects FAs composition, and the way to enhance such mechanisms.